Association of prothrombin complex concentrate administration and hematoma enlargement in non-vitamin K antagonist oral anticoagulant-related intracerebral hemorrhage - Gerner, Stefan Toni; Ringleb, Peter A.; Purrucker, Jan; Rizos, Timolaos (Annals of neurology, 2018)
Objective: To investigate parameters associated with hematoma enlargement in non-vitamin K antagonist oral anticoagulant (NOAC)-related intracerebral hemorrhage (ICH). Methods: This retrospective cohort study includes individual patient data for 190 patients with NOAC-associated ICH over a 5-year period (2011-2015) at 19 departments of neurology across Germany. Primary outcome was the association of prothrombin complex concentrate (PCC) administration with hematoma enlargement. Subanalyses were calculated for blood pressure management and its association with the primary outcome. Secondary outcomes include associations with in-hospital mortality and functional outcome at 3 months assessed using the modified Rankin Scale. Results: The study population for analysis of primary and secondary outcomes consisted of 146 NOAC-ICH patients with available follow-up imaging. Hematoma enlargement occurred in 49/146 (33.6%) patients with NOAC-related ICH. Parameters associated with hematoma enlargement were blood pressure ≥ 160mmHg within 4 hours and - in the case of factor Xa inhibitor ICH - anti-Xa levels on admission. PCC administration prior to follow-up imaging was not significantly associated with a reduced rate of hematoma enlargement either in overall NOAC-related ICH or in patients with factor Xa inhibitor intake (NOAC: risk ratio [RR] = 1.150, 95% confidence interval [CI] = 0.632-2.090; factor Xa inhibitor: RR = 1.057, 95% CI = 0.565-1.977), regardless of PCC dosage given or time interval until imaging or treatment. Systolic blood pressure levels < 160mmHg within 4 hours after admission were significantly associated with a reduction in the proportion of patients with hematoma enlargement (RR = 0.598, 95% CI = 0.365-0.978). PCC administration had no effect on mortality and functional outcome either at discharge or at 3 months. Interpretation: In contrast to blood pressure control, PCC administration was not associated with a reduced rate of hematoma enlargement in NOAC-related ICH. Our findings support the need of further investigations exploring new hemostatic reversal strategies for patients with factor Xa inhibitor-related ICH.
Gesehen am 29.03.2019